Effects of Coronavirus Disease 2019 (COVID-19) on Peripheral Blood Lymphocytes and Their Subsets in Children: Imbalanced CD4+/CD8+ T Cell Ratio and Disease Severity - Shima Mahmoudi; Bahareh Yaghmaei; Meisam Sharifzadeh Ekbatani; Babak Pourakbari; Amene Navaeian; Nima Parvaneh; Mohammad Taghi Haghi Ashtiani; Setareh Mamishi; Setareh Mamishi (Frontiers Media S.A., 2021)
Introduction: While pathogenesis in COVID-19 is not fully known and the effects between SARS-CoV-2 and the immune system are complicated, it is known that lymphopenia, hyper-inflammatory responses, and cytokines play an important role in the pathology of COVID-19. While some hematological abnormalities have been described among the laboratory features of COVID-19, there have not been studies reported on lymphocyte subset analyses in children. The aim of this study was to describe lymphocyte subsets in pediatric patients with mild/moderate or severe COVID-19.Methods: The subjects in the study were children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia confirmed with the real-time RT-PCR. The subjects were admitted to the Children's Medical Center, affiliated with the Tehran University of Medical Sciences, between March 7th and June 10th of 2020. The complete blood counts and lymphocyte subpopulations were analyzed for each patient.Results: The study included 55 hospitalized patients with confirmed SARS-CoV-2 infection (34 patients (62%) with an observed mild/moderate case of the disease and 21 patients (38%) with severedisease). Lymphocyte counts were found to be lower in patients with a severe case (mean ± SD 1.6 ± 0.9 in the severe group vs. 2.3 ± 2.2 in the mild group). Compared to the group with mild/moderate pneumonia, children with severe pneumonia had an increased count of CD8+ T cell and a lower percentage of CD4+ T cell. However, the differences between the groups were negligible. Interestingly, the severe group had a lower CD4+/CD8+ T cell ratio compared to the mild group (1.1 ± 0.47 vs. 1.4 ± 0.8, p-value: 0.063). CD4+/CD8+ T cell ratio <2, 1.5, and 1 was found in 48 (87%), 40 (73%), and 19 cases (35%). All of the seven cases in which the subject passed (13%) had CD4+/CD8+ T cell ratio of <2, 86% had CD4+/CD8+ T cell ratio of <1.5, and 29% had CD4+/CD8+ T cell ratio of <1.Conclusion: The CD4+/CD8+ T cell ratio was lower in patients with severe COVID-19 compared to those with mild/moderate form of disease. However, although a decline in CD4+/CD8+ ratio may serve as a useful metric in analyzing of the derangement in immune responses in patients with severe COVID-19, further study with larger sample sizes is highly recommended.